Peningkatan Pengetahuan Masyarakat Dalam Memahami Tuberkulosis Paru - Zuidah Zuidah; Indah Wati; Srimis Leini Saragih (Cattleya Darmaya Fortuna, 2025)
Pulmonary tuberculosis remains a major public health problem worldwide, including in Indonesia. Limited public knowledge regarding symptoms, transmission, prevention, and treatment adherence contributes to the high incidence and ongoing spread of tuberculosis. This community service activity aimed to improve community knowledge in understanding pulmonary tuberculosis. The method employed was direct health education and socialization conducted at Klinik Pratama Haji Pancing on November 9, 2025. A total of 20 participants were involved in this activity. Educational media included leaflets and interactive health counseling sessions. Evaluation was carried out using pretest and posttest assessments to measure participants’ knowledge levels before and after the intervention. The results showed that prior to the educational intervention, the majority of participants had poor knowledge levels (55%). Following the intervention, all participants (100%) demonstrated a good level of knowledge. These findings indicate that health education through community service activities is effective in improving public understanding of pulmonary tuberculosis. Improved knowledge is expected to encourage healthy behaviors, enhance treatment adherence, and contribute to the prevention and control of tuberculosis transmission within the community.